Tuning Up In Vitro Growth and Development of Cannabis sativa: Recent Advances in Micropropagational Approach - S. M. Ahsan; Md. Injamum-Ul-Hoque; Ashim Kumar Das; Shifa Shaffique; Mehedi Hasan; Sang-Mo Kang; In-Jung Lee; Hyong Woo Choi (Applied Biosciences, 2025)
Cannabis sativa is used for multiple purposes, notably for its medicinal properties. It produces various secondary metabolites, including cannabinoids, terpenes, and flavonoids, which have therapeutic value and typically produce high amounts in female plants. The growth of the global cannabis market has led to intensive breeding efforts to develop elite cultivars with enhanced secondary metabolite profiles. As a dioecious and anemophilous plant, it produces staminate and pistillate inflorescences on separate plants and relies on wind for pollination, rendering traditional propagation methods challenging owing to high genetic recombination in progeny. Consequently, asexual propagation (micropropagation) is commonly employed to maintain female clones entirely. Micropropagation/direct organogenesis is a tissue culture technique that produces numerous disease-free clone plants in vitro more rapidly than traditional rooted cuttings. Factors such as sterilization, hormonal balance, explant type, nutrient additives, carbon source, pH, and environment influence the success of cultivar-specific micropropagation. In this review, we discussed how these factors affect cannabis micropropagation based on recent findings, emphasizing the importance of optimizing cultivar-specific protocols for long-term germplasm conservation and efficient breeding based on a mechanistic background.